A new proposal of the classification of irrigation water - Meireles, Ana; Andrade, Eunice; Chaves, Luiz; Frischkorn, Horst; Crisostomo, Lindbergue (Revista Ciência Agronômica, 2010)
A study on surface water quality in the Acaraú Basin, in the North of the state of Ceará, Brazil was performed. Qualitative dynamics of water flowing to the Acaraú River that supplies water to the irrigation project in the area was evaluated. Multivariate Factor Analysis/Principal Component Analysis was used for evaluation of water quality in order to develop a water quality index (WQI) that reflects soil salinity and sodicity risks and water toxicity to plants. From April/2003 to September/2005 water were sampled from ten sampling sites covering the basin, where physical and chemical parameters that contribute to the WQI were evaluated. The results showed that the use of water for irrigation in the Acaraú basin, according to the proposed WQI, are potentially prone to cause toxicity (crop cycle) and sodicity problem in the long run, if the soil-water-plant is not carefully monitored.